ANALISIS PENGARUH PENGELUARAN PEMERINTAH, INVESTASI, DAN ANGKATAN KERJA TERHADAP PERTUMBUHAN EKONOMI DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TAHUN 2012-2014 (Studi Kasus Pada Kota dan Kabupaten di Jawa Timur) - DINY NIKEN CITRA PANGGALIH (Thesis Ilmu Ekonomi FEB - UB, 2018)
Diny Niken Citra Panggalih: Postgraduate Economics and Business Faculty of Brawijaya University, January 16th 2018. The Effect of Government Expenditure, Investment, And Workforce on Economic Growth and Human Development Index (HDI) Year 2012-2014 (Case Study on City And Regency in East Java). Supervisor: Moh Khusaini, co-supervisor: Susilo. This study aims to analyze the influence of government expenditure, investment, and workforce on economic growthin East Java province with Human Development Index (IPM) as the intervening variable. This research used thequantitative descriptive method. This research studied the secondary data that were consisted of panel data of 38 cities and regencies in East Java during the period 2012-2014. The technique of data collection was literature study and the statistical analysis method was using Path analysis. The results revealed that the variables of government expenditure and investment have apositiveeffect on economic growth ofthe city and regency in East Java. Meanwhile, the variable of workforce has no effect on economic growth. In addition, the variable of economic growth has a positive effect on the HDI, government expenditure variable have a negative effect on the HDI, investment variable has no effect on the HDI, and the variable ofworkforce has no effect on the HDI of the city and regency in East Java Province. Keywords: Government expenditure, Investment, Workforce, Economic growth, HDI